Was Scotland covered by an ice sheet during Marine Isotope Stage 4? Insights from the pre‐Last Glacial Maximum marine terraces of northwest Scotland - Alexander R. Simms; Regina DeWitt; Sarah L. Bradley; Emily Huffman; Louise Best; Tom Bradwell; Jeremy M. Lloyd; Samuel B. Kachuck (Journal of Quaternary Science, 2025)
Raised shorelines provide important constraints on past sea levels, glacial isostatic adjustment (GIA), and rates and directions of vertical crustal motion. Although most raised shorelines across NW Scotland relate to post‐Last Glacial Maximum (LGM) glacial‐isostatic rebound, many undated shorelines lie above the marine limit established from isolation basins. Here, we present new optically stimulated luminescence (OSL) ages for a raised marine terrace at an elevation of 28 m in Slaggan Bay of NW Scotland. Four OSL ages suggest the feature is pre‐LGM, likely Marine Isotope Stage (MIS) 3. Global mean sea levels (GMSL) during MIS 3 are thought to have been ~40–60 m below present across most of the globe. We use a pair of GIA models to determine what ice sheet and sea‐level scenarios might provide an explanation for these anomalously high sea levels during MIS 3. Our results suggest that in the absence of tectonic activity, such high MIS 3 shorelines across NW Scotland require a MIS 4 ice sheet in Scotland, with postglacial rebound of the crustal depression following its demise during MIS 3 responsible for the elevated shoreline features at that time.